Stress, anxiety and uncertainty in EMS provider during COVID-19 - an exploratory study - Sporer, Celia; Resko, Jody (International Journal of Occupational Safety and Health, 2025)
Introduction: EMS providers played a crucial role in the frontline response to the COVID-19 pandemic. Facing challenges and despite their critical role, EMS providers are not given the attention they deserve in research and practical applications. This study examined the early psychological impact of the pandemic on EMS providers. The study assessed the psychological impact of COVID-19 on EMS providers, exploring relationships between workplace stressors, COVID-specific variables, and psychological distress. Findings inform strategies for supporting EMS providers’ mental health. Methods: Data collection, during the early pandemic, involved online recruitment and surveys that included psychological scales, demographics, and COVID-specific variables. Findings: 34 EMS providers from the New York Metro area, mostly working full-time in private agencies, noted significant impacts of COVID-19 on both providers and their workspaces. Although perceived risk and inadequacy of personal protective equipment were noted, the primary COVID-specific variable affecting psychological outcomes was moderate. Psychological measures showed low to moderate distress, mild anxiety (higher in women), and low to moderate perceived stress. Stress correlated with work-related stressors and lower workplace satisfaction. Moderate uncertainty is linked to specific work challenges, while low PTSD scores are associated with poor work culture satisfaction, lack of flexibility, and negative work attitudes. Conclusion: This study challenges assumptions of high stress, anxiety, and PTSD in EMS providers during the early COVID-19 response. Workplace variables, not COVID-specific factors, are more linked to negative psychological symptoms. Recognizing and addressing EMS providers’ mental health needs during high-stress events is crucial, emphasizing the role of general workspace issues.